Kid's eye view of science - Kovalik, Susan J. (Kent, WA : Center for the future of Public Education, 1994)
A Teacher's Handbook for implementing an intergrated thematic approach to teaching science, K-6
Keywords: Science -- Study and teaching; Science -- Handbook